2004
DOI: 10.1158/1078-0432.ccr-1162-03
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks Analysis of Surface-Enhanced Laser Desorption/Ionization Mass Spectra of Serum Protein Pattern Distinguishes Colorectal Cancer from Healthy Population

Abstract: Purpose:The low specificity and sensitivity of the carcinoembryonic antigen test makes it not an ideal biomarker for the detection of colorectal cancer. We developed and evaluated a proteomic approach for the simultaneous detection and analysis of multiple proteins for distinguishing individuals with colorectal cancer from healthy individuals.Experimental Design: We subjected serum samples (including 55 colorectal cancer patients and 92 age-and sexmatched healthy individuals) from 147 individuals, for analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
72
2
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 22 publications
0
72
2
3
Order By: Relevance
“…Chen et al (2004) also detected an elevation of a peak at 8930 m/z in samples from colon cancer patients that may be the same protein. A peak of similar mass was identified as apolipoprotein A-II in prostate cancer samples (Malik et al, 2005) and as a fragment of vitronectin in hepatocellular carcinoma samples (Paradis et al, 2005), underlining the need to validate identifications using independent assays.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Chen et al (2004) also detected an elevation of a peak at 8930 m/z in samples from colon cancer patients that may be the same protein. A peak of similar mass was identified as apolipoprotein A-II in prostate cancer samples (Malik et al, 2005) and as a fragment of vitronectin in hepatocellular carcinoma samples (Paradis et al, 2005), underlining the need to validate identifications using independent assays.…”
Section: Discussionmentioning
confidence: 83%
“…This work identified some of these peaks as transferrin, a1-antitrypsin, complement C3a des-arg and apolipoprotein C1. A similar use of SELDI by Chen et al (2004), Guang et al (2004) and Yu et al (2004) suggested that SELDI profiling could be more sensitive than CEA analysis in diagnosing CRC. The data in this paper support this, but, additionally, identifies potential biomarkers, which require validation with large numbers of patients and if successful could point to the development of more widely applicable immunoassays.…”
Section: Discussionmentioning
confidence: 89%
“…Surface Enhanced Laser Desorption Ionisation-Time of Flight Mass Spectrometry (SELDI-TOF MS) 2,3 is being increasingly used to search for new and better tumour markers in (serum) protein profiles, for example, for ovarian, 4 breast, 5 prostate 6 and colorectal cancer. 7 Its appeal lies in the ease with which a multitude of samples can be analysed with a minimum of sample preparation in a single SELDI-TOF MS analysis. Indeed, SELDI-TOF MS has also been performed to identify biomarker proteins for early detection of RCC.…”
mentioning
confidence: 99%
“…One such approach is proteomic profiling (Adam et al, 2002;Li et al, 2002;Kozak et al, 2003;Poon et al, 2003;Chen et al, 2004;Paradis et al, 2005;Schwegler et al, 2005;Yang et al, 2005;Ward et al, 2006a -c). We and other groups have suggested that patients with HCC may express a characteristic protein 'signature' even in the case of small tumours (Poon et al, 2003;Paradis et al, 2005;Schwegler et al, 2005;Ward et al, 2006a -c).…”
mentioning
confidence: 99%
“…These signatures are customarily detected using Surface-Enhanced Laser Desorption/ Ionisation (SELDI) technology, which permits the mass spectrum of a specific subset of serum proteins to be compared between cancer and non-cancer patients using various pattern recognition programmes. While there has been considerable controversy about the robustness of this approach, particularly with regard to its reproducibility and the techniques used to validate results (Diamandis, 2004;Petricoin et al, 2004;Ransohoff, 2004), a large body of evidence does suggest that such signatures are detectable (Adam et al, 2002;Li et al, 2002;Kozak et al, 2003;Poon et al, 2003;Chen et al, 2004;Paradis et al, 2005;Schwegler et al, 2005;Yang et al, 2005;Ward et al, 2006a -c), even if clinical utility remains to be convincingly shown.…”
mentioning
confidence: 99%